Colorization of Gell-Mann-Nishijima Relation and Mass Principle, Origins of Mass; Fermions and Charges, Bosons and Color-Pairs (Global Journal of Science Frontier Research, 2025)
This paper offers color representation of Gell-mann-Nishijima Relation for quarks and leptons, in which the three quantum numbers, electrical charge, isospin and hypercharge all are colorized into three quantum col ored numbers , and Y. Mass Principle is posulated to account for the mass effect of electrical charge Q. Particle mass M is suggested to be propertional to the scalar products of electrical charge Q of the particle. Further the observed twelve elementary fermion mass spectrum are given, which include those ones of three generation neutrinos. Although neutrinos are neutral particles, but their scalar products could be nonzero values. This paper presents a boson particle color mechanism about electrical charge , with which Higgs boson , and bosons c ould be constructed into the bound states of an elementary fermion and a anti-elementary fermion , each one with an opposite imaginary color of a Color-Pair , Further the masses of these bosons could be obtained by Mass Principle.
Keywords: color of isospin; color of hypercharge; color of electric charge